Quality of cowpea seeds (Vigna unguiculata (L.) Walp.) produced in Paragominas, Pará (Research, Society and Development, 2021)
The production of cowpea seeds in the off-season in the municipality of Paragominas may be a viable alternative, both by the growth potential of this region, as by the proximity to local farmers and the possibility of development and adaptation of cultivars to local climatic conditions. Thus, the present work was developed with the objective of evaluating the seed quality of cowpea bean cultivars produced in Paragominas, Pará, in order to assess the adaptability of cultivars in the city. The experiment was arranged in an entirely randomized design, with four cultivars and five    repetitions. It was evaluated the physical quality (thousand seeds weight, humidity degree and mechanical damage), physiological quality (germination test, first count of germination, accelerated aging, electrical conductivity, seedling emergence in the field and seedling emergence speed index) and seed health quality (test on filter paper). The data obtained were submitted to ANOVA by Shapiro-Wilk and Lilliefors the test, and homogeneity of variances by Levene's test. For data that did not show normal distribution, the Box-Cox transformation was applied test and when significant differences were found between cultivars, the respective means were compared by the Tukey test. The results obtained in this work are possible to produce seeds with high physical, physiological and sanitary quality in Paragominas. The seeds from cultivars 3 and 1 respectively, obtained better results in relation to the other cultivars analyzed, presenting lower rates of mechanical damage, a higher percentage of germination and vigor and lower incidence of fungus.